Temperature and moisture regimes of a soil with onion as affected by conventional or strip tillage systems - Amado, Telmo Jorge C.; Matos, Antônio T. de; Torres, Laércio (Pesquisa Agropecuaria Brasileira, 2014)
To study temperature fluctuation and soil moisture regimes with conventional and strip tillage for onion in a Inceptisol, an experiment was conducted. The conventional tillage was made with one ploughing and two rotative operations; the strip tillage, with furrows of 15cm and 12cm of depth. Space of 25cm between the rows remained covered. In these tillages the temperature fluctuations were recorded using a geothermometer placed at 5 and 10cm above the soil surface, and the soil moisture was taken with a mercury tensiometer installed at 8 and 22 cm. Strip tillage showed maximum temperatures, shorter amplitudes and less temperature fluctuation than did the conventional tillage. The moisture content was also higher for minimum tillage. For the first and third years bulb yield was greater in the strip tillage, although differences were not statistically significant in the second year.